Two-particle Bose-Einstein correlations in pp collisions at √s=13 TeV measured with the ATLAS detector at the LHC - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (The European physical journal. C, Particles and fields, 2022)
This paper presents studies of Bose–Einstein correlations (BEC) in proton–proton collisions at a centre-of-mass energy of 13 TeV, using data from the ATLAS detector at the CERN Large Hadron Collider. Data were collected in a special low-luminosity configuration with a minimum-bias trigger and a high-multiplicity track trigger, accumulating integrated luminosities of 151 μb−1 and 8.4 nb−1, respectively. The BEC are measured for pairs of like-sign charged particles, each with |η|<2.5, for two kinematic ranges: the first with particle pT>100 MeV and the second with particle pT>500 MeV. The BEC parameters, characterizing the source radius and particle correlation strength, are investigated as functions of charged-particle multiplicity (up to 300) and average transverse momentum of the pair (up to 1.5 GeV). The double-differential dependence on charged-particle multiplicity and average transverse momentum of the pair is also studied. The BEC radius is found to be independent of the charged-particle multiplicity for high charged-particle multiplicity (above 100), confirming a previous observation at lower energy. This saturation occurs independent of the transverse momentum of the pair.